Annular pancreas presenting as gastric outlet obstruction in an adult: a case report - Rabindra KC (Society of Surgeons of Nepal, 2017)
Annular pancreas is a rare congenital abnormality which arises in the embryo by persistence of pancreatic tissue in the track which the ventral pancreatic bud follows in its rotation round the duodenum.  A 21 years old male was admitted because of a non bilious vomiting and epigastric fullness after intake of food. Diagnosis was confirmed with contrast enhanced CT scan of the abdomen. He successfully underwent laparoscopic gastrojejunostomy with uneventful postoperative recovery. Though rare, annular pancreas should be considered as differential diagnosis in patient presenting as gastric outlet obstruction after excluding common causes.